Diabetes insipidus in neuropsychiatric-systemic lupus erythematosus patient - Pangestu, Y; Wardoyo, A; Wijaya, Linda K; SETIYOHADI, BAMBANG; Albar, Zuljasri; Sukmana, N; Budiman, Budiman; Djoerban, Z; Effendy, S; Aziza, L; Sitorus, F (Indonesian Rheumatology Association, 2010)
Systemic lupus erythematosus (SLE) is an idiopathic autoimmune chronic inflammatorydisease that is unique in its diversity of clinical manifestations, variability of diseaseâs progression, and prognosis. The disease is characterized by the remission and multiple flare-ups in between the chronic phase that may affect many organ systems.The prevalence of SLE in the US population is 1:1000 with a woman to man ratio of about 9-14:1. At Cipto Mangunkusumo Hospital, Jakarta in 2002, there was 1.4% cases of SLE of the total number of patients at the Rheumatology Clinic. Neuropsychiatric manifestations of SLE (NP-SLE) have a high mortality and morbidity rates. The incidence of NP-SLE ranges 18-61%. Diagnosis of NP-SLE is difficult because there is no specific laboratory examination. Accordingly, in all SLE patients with central nervous system (CNS) dysfunction, additional tests will be necessary to confirm an NP-SLE diagnosis and exclude other causes.Â Similar to diabetes insipidus, SLE is a systemic disease which affects many organ systems, one being the endocrine system. No data has specified the occurrence rate of diabetes insipidus in SLE patients. This disease arises from a number of factors able to interfere with the mechanism of neurohypophyseal renal reflex resulting in the bodyâs failure to convert water.3 There are three general forms of the disease, a polydipsicpolyuric syndrome caused by partial/complete vasopressin deficiency (central-diabetes-insipidus/CDI), vasopressin resistance of the kidney tubules (nephrogenic-diabetes-insipidus/NDI), and primary polydipsia. CDI occurs in about 1 in 25,000 persons